Peran Kepala Sekolah dalam Meningkatkan Budaya Kerja Para Guru Sekolah Dasar - Selvia, Tisna Ayu; Putra, Sofwan Adi; Badrun, M. (Universitas Muhammadiyah Surakarta, 2024)
A positive work culture in the school environment is a key element in improving the quality of education. This study aims to analyse the role of school principals in building a teacher's work culture at SD Negeri 2 Kuripan, focusing on five main aspects: discipline, cooperation, commitment, creativity, and professionalism. The research method used is a case study with a qualitative approach, involving in-depth interviews, participatory observation, and document analysis. The results of the study show that school principals play a central role in creating a conducive work environment. The principal encourages discipline through exemplary and fair application of rules, facilitates cooperation through collective activities, and strengthens teachers' commitment by providing appreciation and emotional support. In addition, creativity and innovation are encouraged through the provision of facilities and the freedom to experiment, while teachers' professionalism is enhanced through continuous training and effective monitoring. The conclusion of this study confirms that strategic, inclusive, and vision-based leadership of school principals can significantly improve teachers' work culture. The recommendations are directed at strengthening professional development, internal communication, and a culture of innovation to support the sustainability of improving the quality of education.